APLIKASI SELULOSA BAKTERIAL-DIETILENTRIAMINA SEBAGAI LAPISAN PENGIKAT LOGAM Pb DAN Cd PADA METODE DIFFUSIVE GRADIENT IN THIN FILMS (DGT) - Khairuddin Khairuddin; Prismawiryanti Prismawiryanti; Indriani Indriani (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
This research aimed to synthesis and apply of bacterial cellulose-diethylenetriamine as a binding layer on the diffusive gradients in thin films method for preconcentration of labile metal Pb and Cd in aquatic systems and sediment of Palu Bay. The results are expected to be used for the analysis of environmental contaminants aquatic pollutant/sediment replace conventional methods. DGT method easily carried into the field and sensitive to identify certain metal ions. The results showed concentration of heavy metals dissolved in seawater for Pb between 0.024 to 0.048 mg / L, while for Cd between 0.006 to 0.015 mg / L. The concentration of Pb in sediments from 7.426 to 16.043 mg / L and Cd 0.387 to 0.950 mg / L. Partial regression analysis between Pb and Cd concentrations in water with a concentration of cadmium metals Pb and Cd in the sediments showed that the concentration of heavy metals in water has a positive correlation with the concentration of Pb and Cd in the sediment.Keyword: Pb, Cd, DGT, bacterial cellulose-diethylenetriamine, Palu Bay